Age Limit For Presidential and Vice Presidential Candidates in the Constitutional Court Decision Number 90/PUU-XXI/2023; A Legal Approach - Rochmawanto, Munif; Suisno; Sakuroikan, Zainal Hamdan (Jurnal Independent, 2024)
ABSTRACT The Constitutional Court decision Number 90/PUU-XXI/2023 has sparked controversy. The reason is, many parties are linking this decision with the son of the President of the Republic of Indonesia who will be a Presidential Candidate in 2024, namely Gibran Raka Bumingraka, who is still under 40 years old. As for the discussion of this research, the researcher focuses on discussing the considerations of Constitutional Court judges in decision Number 90/PUU-XXI/2023 regarding the age limit for Presidential-Vice Presidential Candidates, and how the juridical review of the considerations of Constitutional Court judges in decision Number 90/PUU-XXI/2023 regarding the age limit for presidential and vice presidential candidates. The type of research in writing this thesis is normative legal research, with a statutory approach (statue approach). The results of this research are as follows; First, in consideration of the Constitutional Court decision Number 90/PUU-XXI/2023 there are different reasons (concurring opinion) from 2 (two) Constitutional judges, namely; Constitutional Justice Enny Nurbaningsih and Constitutional Justice Daniel Yusmic P. Foekh, and there are also different opinions (dissenting opinion) of 4 (four) Constitutional Justices, namely; Constitutional Justice Wahiduddin Adams, Constitutional Justice Saldi Isra, Constitutional Justice Arief Hidayat, and Constitutional Justice Suhartoyo. Second, the decision of the Constitutional Court Number 90/PUU-XXI/2023 is not in line with Article 51 Paragraph (3) letter b of Law Number 24 of 2003 concerning the Constitutional Court, which regulates the material review of the content of paragraphs, articles and/or Parts of the Law that are deemed to be in conflict with the 1945 Constitution may be requested to be declared as having no legal binding force.